2021
DOI: 10.1039/d0cc07374a
|View full text |Cite
|
Sign up to set email alerts
|

Chirality in porous self-assembled monolayer networks at liquid/solid interfaces: induction, reversion, recognition and transfer

Abstract: The article describes chirality induction and reversal, recognition in bilayer formation and transfer in grafting to the basal graphitic surface relevant to the porous self-assembled monolayer networks formed by chiral triangular building blocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 96 publications
(149 reference statements)
0
15
0
Order By: Relevance
“…This chirality is defined by the position of the grafted molecules with respect to the symmetry axes of the graphite substrate they are covalently attached to. 46 Furthermore, this chirality transmission proceeds in a homochiral manner using the homochiral porous SAMN formed by a chiral DBA derivative as a template. 42,47 The advantages of this template-guided nanopatterning are its convenient procedure under ambient conditions and the ability to tailor the spacing, symmetry, and chirality of the grafted network based on the choice of the SAMNs.…”
Section: Introductionmentioning
confidence: 99%
“…This chirality is defined by the position of the grafted molecules with respect to the symmetry axes of the graphite substrate they are covalently attached to. 46 Furthermore, this chirality transmission proceeds in a homochiral manner using the homochiral porous SAMN formed by a chiral DBA derivative as a template. 42,47 The advantages of this template-guided nanopatterning are its convenient procedure under ambient conditions and the ability to tailor the spacing, symmetry, and chirality of the grafted network based on the choice of the SAMNs.…”
Section: Introductionmentioning
confidence: 99%
“…1 To date, the careful design and synthesis of molecular building blocks have been attempted to develop well-organised two-dimensional molecular networks, which are formed through non-covalent interactions such as hydrogen bonding, metal coordination, dispersion forces, and halogen bonding. 2 The direct visualisation and analysis of such two-dimensional structures at the molecular level can be achieved by scanning tunnelling microscopy (STM). 2 By means of such observations, it has been found that the direction of the supramolecular interaction sites and the use of characteristic molecular shapes have produced various intriguing two-dimensional structures at the solid/liquid interface.…”
Section: Introductionmentioning
confidence: 99%
“…2 The direct visualisation and analysis of such two-dimensional structures at the molecular level can be achieved by scanning tunnelling microscopy (STM). 2 By means of such observations, it has been found that the direction of the supramolecular interaction sites and the use of characteristic molecular shapes have produced various intriguing two-dimensional structures at the solid/liquid interface. 3 In addition, several factors have been demonstrated to affect the final two-dimensional assemblies, such as the solvent type, temperature, concentration, and alkyl chain length (odd–even effect), and the electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the alkylation of rigid molecules can alter their physical properties [1][2][3][4][5][6][7][8][9][10][11] significantly, including their thermal properties, [12][13][14][15] crystal structure, [16][17][18][19][20][21] and the structure of adsorbed monolayers. [22][23][24][25][26][27][28] We have analyzed the thermal properties of salen derivatives bearing alkyl chains of variable length and found that those with alkoxy groups adopt a liquid crystalline state at varying temperatures depending on the alkyl chain length. 29,30 In contrast, OC12-salpn, a salen derivative with a methyl group introduced as steric bulk, exhibited cold crystallization.…”
Section: Introductionmentioning
confidence: 99%